W. R. Rest, The Inns of Court under Elizabeth I and the Early Stuarts - Izdebski, Hubert (Czasopismo Prawno-Historyczne, 1974)
Recenzja: Wilfrid R. Rest, The Inns of Court under Elizabeth I and the Early Stuarts, 1590-1640, London 1972, Longman Group Ltd., s. XII+264.